Cuba Varas, Lucero and Elisa Juárez Chávez. Growing up being different: compilation of three investigations on homophobic, transphobic and lesbophobic violence in the family and school in Peru. Lima: PROMSEX, 2018,168 pp. - Ramos López, José (2020)
The main findings of “Growing up while being different” are presented while paying special attention to political recognition of difference and homophobic violence. Relevance and pending research activities are shown.